ANALISIS KEPUASAN PENGGUNA JAMINAN ASURANSI KESEHATAN MANDIRI IN HEALTH PADA PENGGUNA MANDIRI IN HEALTH DI PT PEGADAIAN PERSERO CABANG MAMUJU - Ramisa, Ramisa; Ilyas, Muh.; Zamli, Zamli (Ensiklopedia of Journal, 2024)
Abstract: This research discusses the influence of Mandiri In Health Health Insurance Guarantee User Satisfaction on Mandiri in Health users at PT. Pawnshop company Mamuju Branch. This research uses the Analytical Survey method. This research uses a cross sectional approach. The population was 43 people, the research sample was 30 employees. The sample technique uses accidental sampling. Chiss square test analysis. The research results show that there is a relationship between Reliability and the X2 Calculate value, namely 8.167 and the significant value is sig-p = 0.004 < 0.05, Responsiveness with the X2 Calculate value, the significant value of the probability of responsiveness is sig-p = 0.004 < 0.05, Tanggible with The calculated X2 value is 8.167 and the tangible probability significant value is sig-p = 0.004 < 0.05, the assurance with the calculated X2 value is 10.804 and the significant probability value is sig-p = 0.001 < 0.05. empathy with a calculated X2 value of 10.804 and a significant value of sig-p = 0.001 < 0.05 on patient satisfaction using Mandiri In Health insurance at PT. Pawnshop company Mamuju Branch in 2024.Keywords: Patient satisfaction, reliability, responsiveness, tangible, assurance, empathy.